Optimizing the talent management and evaluation process in technology companies using web systems - Fernández-Paredes, María Isabel; Rodríguez-Santos, Marycarmen; Linares-Grijalva, Karin Dessire (AiBi Journal of Research, Administration and Engineering, 2025)
The adoption of web-based systems for talent management and evaluation has become a fundamental element in technology- driven organizations, where competitiveness and efficiency are crucial. This systematic review aims to assess the best technological platforms for optimizing the efficiency and effectiveness of the personnel selection process. To achieve this, the Scopus database was used, from which 215 articles were retrieved. Applying the PRISMA methodology, a detailed analysis of the literature on the Optimization of the Talent Management and Evaluation Process in Technology Companies through Web-Based Systems was conducted. Initially, 75 articles related to this topic were examined, and after applying selection and exclusion criteria, 52 relevant articles were chosen for this study. The results showed that web-based systems, through algorithms and data analysis, enable a faster and more accurate assessment of candidates, reducing both the time and resources invested in the recruitment process. The most efficient technique was the integration of chatbots and advanced data visualization, which allowed for a quicker and more precise pre-selection of candidates, reducing hiring time by 20%. It was concluded that the implementation of these systems not only optimizes the recruitment process but also contributes to improving overall employee performance and the company’s operational efficiency. Investing in these technologies can make a significant difference in the long-term success of organizations in a highly competitive market.